The Impact of Remittances from Overseas Workers on Economic Expansion at Home: Evidence from Bangladesh (Global Journal of Management and Business Research, 2022)
The purpose of this research is to determine whether or not the money that Bangladeshi migrant workers send back to their families has an impact on the overall pace of economic growth in Bangladesh. The multiple regression model is used as an analytical technique in this study to estimate yearly timeseries data and parameters from 1999 to 2021. The study covers the time period from 1999 to 2021. The data from realworld applications provides credence to the theory that there is a significant and beneficial connection between the money that migrant workers send back to their families and the expansion of the economy. Other alterations in rules, such as those concerning gross capital creation and the size of the labor force, are also statistically significant. However, direct foreign investment is not included in these alterations. This article examines some significant research that demonstrates the significance of remittances sent by migrant workers as a means of contributing to the expansion of the economy. In addition, the length of the research, the estimating methodologies that were employed, as well as the variability of the controls, were all different from those that were used in prior studies. In conclusion, the empirical findings that have been developed are quite sound.
Keywords: remittances; migrant workers; economic growth; capital creation